Identification of QTLs/ Candidate Genes for Seed Mineral Contents in Common Bean (Phaseolus vulgaris L.) Through Genotyping-by-Sequencing - Nazir, Muslima; Mahajan, Reetika; Mansoor, Sheikh; Rasool, Sheezan; Mir, Rakeeb Ahmad; Singh, Ravinder; Thakral, Vandana; Kumar, Virender; Sofi, Parvaze A.; El-Serehy, Hamed A.; Hefft, Daniel Ingo; Zargar, Sajad Majeed (Frontiers in Genetics, 2022)
Throughout the ages, the common bean has been consumed by humanity as an important food staple crop and source of nutrition on a global scale. Since its domestication, a wide spectrum of phenotypic and genotypic investigations have been carried out to unravel the potential of this crop and to understand the process of nutrient accumulation along with other desirable characteristics. The common bean is one of the essential legume crops due to its high protein and micronutrient content. The balance in micronutrients is critical for the growth and development of plants as well as humans. Iron (Fe), Zinc (Zn), Copper (Cu), Manganese (Mn), Magnesium (Mg), Calcium (Ca), and Molybdenum (Mo) are some of the important micronutrients present in legumes. Thus, we aimed to investigate the quantitative trait loci’s (QTLs)/single nucleotide polymorphisms (SNPs) to identify the candidate genes associated with micronutrients through genotyping by sequencing (GBS). In our investigation, through GBS we identified SNPs linked with traits and assessed seven micronutrients in 96 selected common bean genotypes for screening nutritionally rich genotypes. Among 96399 SNPs total identified through GBS, 113 SNPs showed significant phenotypic variance, ranging from 13.50 to 21.74%. SNPs associated with most of the seed micronutrients (Mg, Mn, Fe, Ca, Cu) were found on chr3 & chr11 (Mg, Mn, Mo, Ca, Zn). The findings from this study could be used for haplotype-based selection of nutritionally rich genotypes and for marker-assisted genetic enhancement of the common bean. Further, the identified SNPs for candidate genes/transporters associated with micronutrient content may pave the way for the enrichment of seeds by employing genomics-assisted breeding programs.